The Digital Competence in the University Teacher - Ocaña-Fernández, Yolvi (2020)
Digital skills in the work of higher education is a very fruitful field that is constantly developing due to the adequacy of teachers in the face of the demand for information and communication technologies and their impact on the educational field. This article deals with the current panorama and its dynamics against the requirements that the teacher must develop and the perspectives of the university and students. On the other hand, the perspective of new trends in relation to the panorama of virtual learning environments and their link in university education, is addressed. In addition, a final discussion is presented on the possibilities of the development of competencies in the higher academic task.